"A Very Bad Presidente in the House": Workhouse Masters, Care, and Discipline in the Eighteenth-Century Workhouse. Issue 4 (24th April 2020) - Ottaway, Susannah
Abstract: Although they linger in historical memory as "Pauper Bastilles, " in the long eighteenth century, English workhouses functioned in many ways as institutions of care, as well as places of discipline. This article uses an unusual set of source materials—including a Master's Query Book—to examine the nature of workhouse discipline in the Leeds township workhouse in the mid-eighteenth century. A close analysis of this remarkable source allows us a clear view of both the structures of authority and the agency of poor inmates in this institution. Poor Law officials monitored material conditions in the workhouse—the provision of food, clothing, and medical care—with great attentiveness, ensuring inmates were kept in good health, while leaving records that reveal intensive surveillance of the material objects inside the house. The workhouse committee also, however, kept an eagle eye on the workhouse master, allowing inmates a direct line of complaint. Workhouse inmates responded to these conditions by vigorously resisting rules that restricted their freedom of movement inside and outside the institution. Masters in such institutions were intermediaries between parish governors and the poor, rather than "technicians of discipline." At the same time, workhouse records show that children were far more vulnerable, subjected to discipline at the discretion of master and mistress; we must disaggregate their experiences from the general population of inmates. These findings conform well to a widening strand in the historiography that reveals Old Poor Law workhouses as complex, hybrid institutions.